States of trauma : gender and violence in South Asia - Chatterjee, Piya, 1965-; Desai, Manali, 1966-; Roy, Parama (Zubaan, 2009)
In the last couple of decades, violence as an analytic category has loomed large in the historical, literary, and anthropological scholarship of South Asia. The challenge of thinking violence in its gendered incarnations fully and in all its complexity is not only theoretical or critical but also irreducibly ethical and political, given the proliferation of civil wars, pogroms and riots, fundamentalist movements, insurgencies and counterinsurgencies, and new technologies of violence and injury. All of these simultaneously feature and help constitute gendered actors and gendered scripts of violence. States of Trauma seeks to examine this terrain by staging a set of questions. How are we to think about the moral charge that accrues to violence? What is the relationship between violence and non-violence? In considering the moral and affective economy of violence, how may we speak of the seductions of the idioms and practices of militarism and sexualized violence for women? How are these seductions/pleasures distinct from those proffered to men, if indeed they are distinct?